Strategi Komunikasi dalam Pemasaran Pariwisata Berbasis Digital Tourism di Kabupaten Tapanuli Tengah - Tanjung, Hasrudy; Tanjung, Irwan Syari; Astuti, Rini (PERSPEKTIF, 2024)
Digital tourism is the main strategy in promoting tourism destinations in Central Tapanuli Regency through the "Pesona Tapanuli Tengah" application and other digital platforms. However, challenges such as lack of attention from local governments and limited human resources in information technology are still issues. This study designed a digital-based tourism marketing model and identified factors influencing the low mastery of information technology among tourism human resources. Through a qualitative descriptive approach, this study highlights that the "Pesona Tapanuli Tengah" application and digital marketing strategy have a positive impact on increasing tourist interest. However, local governments, tourism industry players, and local communities need collaborative efforts to address these challenges. By continuing to improve digital marketing strategies and increasing digital literacy among the community, it is hoped that the tourism potential of Central Tapanuli Regency can be maximized, providing significant economic benefits for the local community.